The Weighting Problem in Testing the Linkage Hypothesis - Laumas, Prem S. (Quarterly Journal of Economics, 1976)
Journal Article The Weighting Problem in Testing the Linkage Hypothesis Get access Prem S. Laumas Prem S. Laumas Northern Illinois University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 90, Issue 2, May 1976, Pages 308–312, https://doi.org/10.2307/1884632 Published: 01 May 1976